Evaluation of the frost tolerance of Hungarian-bred walnut cultivars - Szügyi-Bartha, Krisztina; Bujdosó, Géza; Froemel-Hajnal, Veronika; Szügyi, Sándor; Stefanovits-Bányai, Éva; Szalay, László (Acta Biologica Szegediensis, 2022)
At present very few walnut cultivars can be said to be cosmopolitan cultivars, grown widely in the walnut-producing countries of the world. Walnut (Juglans regia L.) has poor ecological adaptability, as its cultivation is greatly influenced by low temperatures during the winter dormancy period and in early spring. The breeding activities conducted in various countries are therefore of great significance. Choosing suitable locations for cultivation is of key importance if optimum yield stability is to be achieved. The introduction of foreign walnut cultivars regularly runs into problems if, despite their high yielding ability, they are unable to adapt to the Hungarian climate. In Hungary the most critical weather events for walnuts are the frequent frosts in early spring. Buds therefore need to burst late to avoid damage to the flowers. Many papers have dealt with the frost tolerance of stone fruit, but only limited information has been published on the frost tolerance of walnut. For the first time in Hungary, artificial freezing tests were performed in the present work to determine the frost tolerance of the cultivars available in Hungary. The results could be of service to Hungarian growers in choosing the most suitable cultivar.